Find the relation of the variable w if the growth rate is given by
dw/dt=(kw(α-w))/α, k>0, at t=0,w=α/(1+β)
Let us find the relation of the variable "w" if the growth rate is given by
"\\frac{dw}{dt}=\\frac{kw(\u03b1-w)}{\u03b1},\\ \\ k>0," at "t=0,\\ w=\\frac{\u03b1}{1+\u03b2}."
It follows that
"\\frac{\\alpha dw}{w(\u03b1-w)}=kdt"
"\\int\\frac{\\alpha dw}{w(\u03b1-w)}=\\int kdt"
"\\int(\\frac{1}{\u03b1-w}+\\frac{1}{w})dw=\\int kdt"
"\\ln|w|-\\ln|\\alpha -w|=kt+C_1"
"\\ln|\\frac{w}{\\alpha -w}|=kt+C_1"
"\\frac{w}{\\alpha -w}=C_2e^{kt}"
"w=C_2e^{kt}(\\alpha -w)"
"w=C_2e^{kt}\\alpha -wC_2e^{kt}"
"w (1+C_2e^{kt})=C_2e^{kt}\\alpha"
"w =\\frac{C_2\\alpha e^{kt}}{1+C_2e^{kt}}"
Since at "t=0,\\ w=\\frac{\u03b1}{1+\u03b2}," we have that
"\\frac{\u03b1}{1+\u03b2}=\\frac{C_2\\alpha}{1+C_2}"
"\\frac{1}{1+\u03b2}=\\frac{C_2}{1+C_2}"
"1+C_2=C_2+\\beta C_2"
"1=\\beta C_2"
"C_2=\\frac{1}{\\beta}"
We conclude that
"w =\\frac{\\frac{1}{\\beta}\\alpha e^{kt}}{1+\\frac{1}{\\beta}e^{kt}}=\\frac{\\alpha e^{kt}}{\\beta+e^{kt}}."
Comments
Leave a comment